Discriminating quantum field theories in non-inertial frames. (12th January 2015) - Doukas, Jason; Adesso, Gerardo; Pirandola, Stefano; Dragan, Andrzej
Abstract: Quantum channel discrimination is used to test quantum field theory in non-inertial frames. We search for the optimal strategies which can best see the thermality of the Unruh effect. We find that the usual strategy of counting particles in the vacuum can be improved, thereby enhancing the discrimination. Coherent state probes, which are practical and feasible, give exponential improvement in the discrimination of the Unruh channel and come very close to optimal. In particular, we show that by using a short pulse laser, the accelerations required to test the Unruh effect can be reduced by at least three orders of magnitude with the same statistical confidence as could be achieved in the vacuum. These results are expected to be relevant to upcoming experimental tests of quantum field theory in curved spacetimes in analogue systems.